2018
DOI: 10.1108/el-08-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Web and ontology-based applications for digital libraries

Abstract: Purpose The purpose of this paper is to explore useful Semantic Web technologies and ontology-based applications for digital libraries. It also investigates the perceptions of university librarians and academicians in Pakistan about Semantic Web technologies and their use in digital libraries. Design/methodology/approach An exploratory research design based on Delphi research strategy was conducted to answer the research questions. Interviews were conducted with a purposive sample of 50 key informants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Khan and Bhatti (2018) have conducted a survey of the perceptions of university librarians and academicians in Pakistan about the usefulness of the Semantic Web for digital libraries. Because the Semantic Web enhances the ability of computers to search databases by using artificial intelligence and fuzzy logic, respondents were asked specifically about artificial intelligence software agents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khan and Bhatti (2018) have conducted a survey of the perceptions of university librarians and academicians in Pakistan about the usefulness of the Semantic Web for digital libraries. Because the Semantic Web enhances the ability of computers to search databases by using artificial intelligence and fuzzy logic, respondents were asked specifically about artificial intelligence software agents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Warraich and Rorissa (2020) studied a developing country (Pakistan), finding that the lack of awareness and skills among information professionals and non-compatibility of traditional cataloguing standards with LD pose barriers to its implementation. Some studies (Khan and Bhatti, 2018;Park and Tosaka, 2017) suggested that training and continuing education are essential to promoting LD initiatives in libraries. In short, LD is becoming increasingly popular and used in the LAM community.…”
Section: From Open Data Linked Data To Linked Open Datamentioning
confidence: 99%
“…In the LAM community, Semantic Web has become a topic of considerable interest, especially in the development of digital libraries. Khan and Bhatti (2018) found great benefits in digital libraries developing semantic relationships among digital content and increasing their accessibility to the Web environment. The study also recommended that librarians learn the use of ontology-based applications, such as ontology editing tools.…”
Section: Semantic Webmentioning
confidence: 99%
“…Moreover, they discussed the future challenges and introduced their vision on how MAS and BCT could be combined in different application scenarios. Khan and Bhatti [19] aimed to test the use of semantic web technologies for digital libraries. They also investigated the conceptions of university academicians and librarians in Pakistan in relation to semantic web technologies and their uses in digital libraries.…”
Section: Related Workmentioning
confidence: 99%